Polarimetric beamforming comparison of the multipath clusterization of ML estimates and the measurement data of a MIMO macrocell channel - Materum, Lawrence Y. (Animo Repository, 2010)
Clusters produced by multipath clusterization were comparatively evaluated using the directional power spectrum of the measured channel, which was obtained by polarimetric beamforming due to the dual-polarized nature of the channel sounding data. The clusters were from the results of the clusterization of maximum-likelihood-based path parameter estimates of a macrocell channel. The approach provides a way to render the physical meaning of clustering results in line with the measured channel. The result shows some slight offset from the measured channel, nevertheless, the cluster locations were comparable.